Identification of Genes That Result in High Mortality of Oryctes rhinoceros (Scarabaeidae: Coleoptera) When Targeted Using an RNA Interference Approach: Implications for Large Invasive Insects. (16th March 2020) - Watanabe, Shizu; Adams, Brandi-Leigh; Kong, Alexandra; Masang, Nelson; Vowell, Tomie; Melzer, Michael
Abstract: Coconut rhinoceros beetle, Oryctes rhinoceros (L., 1758), is a large scarab beetle native to Southeast Asia and a major pest of coconut ( Cocos nucifera ) and oil ( Elaeis guineensis ) palms in its invaded range. Few tools are available for coconut rhinoceros beetle management, particularly for an emerging haplotype with resistance to known strains of Oryctes rhinoceros nudivirus, the traditional biological control agent used in coconut rhinoceros beetle management programs. RNA interference (RNAi) represents an emerging tool for insect pest control that exploits an existing pathway for gene regulation in the target organism. In this study, we evaluated RNAi as a potential tool for coconut rhinoceros beetle management. Using transcriptome data generated from gut tissue of early instar larvae, we identified 24 RNAi target sequences that were either highly expressed or had demonstrated efficacy in other insect systems. Double-stranded (ds)RNAs ranging from 249 to 297 bp in length were generated for 23 of these target sequences and 150 ng were microinjected into coconut rhinoceros beetle 1 st, 2 nd, and 3 rd instar larvae and adults. Five of these dsRNAs that targeted genes putatively encoding V-type ATPase, polyadenylate binding protein, and three forms of actin induced 30.8–100% mortality within 14 days post injection (dpi). Microinjection of 2nd instars with 10 and 100 ng of these same five dsRNAs induced 20–100% and 80–100% mortality at 7 and 14 dpi, respectively. These results indicate RNAi should be explored as a possible management option for coconut rhinoceros beetle. Coconut rhinoceros beetle may also represent a model species for using RNAi in the management of large invasive insect species.